PANDANGAN AL-QUR’AN MENGENAI BANK ASI - Shofiatul Jannah, Shofiatul Jannah (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2020)
This research aims to determine the views of the Qur'an regarding the legal status of ASI banks. Therefore, this study is expected to provide answers to the controversy that occurred. This research method is a library research method, namely a method of reviewing written data both books, literature and notes and reports that have a correlation with the discussion. This research uses descriptive-analytic method, namely using existing sources, then describing it, then analyzing how "the view of the Qur'an about ASI banks". In addition, this research also uses a thematic method by determining the theme and collecting verses about breastfeeding and ordering them according to the order of asbāb al-Nuzūl. The results of this study conclude that the ASI bank law is the same as raḍā'ah, that is, it causes the mahram law, so the ASI Bank is prohibited on the grounds that the ASI bank will confuse the nasab. This is based on the word of Allah SWT surah al-Nisa 'verse 23 "and your mothers who breastfeed you". The word "breastfeed" in the verse uses the verb and the verb is absolute so that it indicates the mother's status can be determined by one feeding. Therefore, the impact of breastfeeding is that it is like a nasal relationship, so it is forbidden to marry a breastfeeding mother and all her relatives who have a nasal relationship with those who are breastfeeding, either directly or indirectly.